Flow diverters as a scaffold for treating direct carotid cavernous fistulas. (2nd July 2019) - Baranoski, Jacob F; Ducruet, Andrew F; Przbylowski, Colin J; Almefty, Rami O; Ding, Dale; Catapano, Joshua S; Brigeman, Scott; Fredrickson, Vance L; Cavalcanti, Daniel D; Albuquerque, Felipe C
Abstract : Background: Direct carotid–cavernous sinus fistulas (dCCFs) are high flow arteriovenous shunts between the internal carotid artery and the cavernous sinus. Recently, we have used the pipeline embolization device (PED) to treat dCCFs. Methods: We describe our experience treating patients with dCCFs in whom the PED was placed as the primary treatment modality. Results: Five patients with dCCFs were treated with PEDs deployed in the ipsilateral internal carotid artery spanning the fistula. All patients also underwent either adjunctive transvenous or transarterial embolization. The PED served both as the primary treatment modality and as a scaffold that facilitated safe and efficacious transvenous embolysate administration by altering the flow dynamics through the fistula and providing a physical barrier that protected the internal carotid artery. No intraoperative or perioperative complications occurred. One of the five patients exhibited complete angiographic resolution of the fistula immediately after the procedure. The remaining four patients experienced complete obliteration of the fistula without additional treatment, which suggests that the PED induced alteration promoted thrombosis of the fistula. Therefore, 100% of patients in this series exhibited complete and durable obliteration of the fistula and complete resolution of symptoms following treatment. Conclusions: We believe that use of the PED to treat dCCFs may be a safe and efficacious strategy that facilitates parent vessel protection during transvenous embolization. Furthermore, the flow alterations induced by the PED may promote thrombosis of incompletely occluded fistulas. This is the largest reported series of non-iatrogenic dCCFs treated with use of the PED as the primary initial treatment strategy.